Do High Interest Rates Defend Currencies during Speculative Attacks? - Kraay, Aart (World Bank, Washington, DC, 2014)
Drawing on evidence from a large sample of speculative attacks in industrial and developing countries, the author argues that high interest rates do not defend currencies against speculative attacks. In fact, there is a striking lack of any systematic association between interest rates and the outcome of speculative attacks. The lack of clear empirical evidence on the effects of high interest rates during speculative attacks mirrors the theoretical ambiguities on this issue.